2014
DOI: 10.1037/per0000024
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the perceptions of social network characteristics associated with grandiose and vulnerable narcissism.

Abstract: Two dimensions of narcissism exist, grandiose and vulnerable, which are thought to be associated with distinctly different patterns of interpersonal behavior. Social network analysis is a way of quantifying and analyzing interpersonal interactions that may prove useful for characterizing the networks associated with these narcissism dimensions. In the current study, participants (N = 148) completed scales assessing both narcissism dimensions and a measure of the five-factor model of personality. Egocentric net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 40 publications
1
38
0
2
Order By: Relevance
“…The observed pattern of tolerance but not necessarily likability may help to explain the moderate levels of homophily present for couples where personality pathology is present (e.g., Lavner et al, ). Seeing traits as “less dislikable” does not mean, of course, that individuals would be attracted to or seek out potential friends or romantic partners with these traits; instead, individuals with these more problematic traits may not be as quick to exclude individuals with these same traits from their social networks (e.g., Lamkin et al, ). For example, friends who have similar narcissism scores are likely to have similar scores on other personality variables (Maaß, Lämmle, Bensch, & Ziegler, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed pattern of tolerance but not necessarily likability may help to explain the moderate levels of homophily present for couples where personality pathology is present (e.g., Lavner et al, ). Seeing traits as “less dislikable” does not mean, of course, that individuals would be attracted to or seek out potential friends or romantic partners with these traits; instead, individuals with these more problematic traits may not be as quick to exclude individuals with these same traits from their social networks (e.g., Lamkin et al, ). For example, friends who have similar narcissism scores are likely to have similar scores on other personality variables (Maaß, Lämmle, Bensch, & Ziegler, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multidimensional perceiver effects (Srivastava, Guglielmo, & Beer, ) such as those based on the FFM (e.g., McCrae & Costa, ) have been found. For example, narcissistic individuals were more likely to rate the members of their social network as narcissistic, self‐centered, unlikable, and unkind (Lamkin, Clifton, Campbell, & Miller, ). In addition to these perceiver effects, individuals have a tendency to assume that others are similar to themselves, which is also referred to as assumed similarity .…”
Section: Antagonistic Individuals Rate Other People As More Antagonismentioning
confidence: 99%
“…It did not elucidate mediators of the observed interpersonal effects, such as concrete behavioral processes. It seems possible that charming, and aggressive behaviors account for the links between narcissism and (un)popularity Leckelt et al, 2015) and that empathic and prosocial behaviors account for the link between EI and popularity.…”
Section: Discussionmentioning
confidence: 99%
“…In their effort to maintain a positive sense of self, people with high levels of narcissism often denigrate others, and as a result experience significant dislike from those around them at longer acquaintance. Their low communal focus and high antagonism (Czarna, Czerniak, & Szmajke, 2014;Czarna, Jonason, Dufner, & Kossowska, 2016;Lamkin, Clifton, Campbell, & Miller, 2014) might be discouraging to freshly won friends. Indeed narcissism predicts initial popularity (Back, Schmukle, & Egloff, 2010;Carlson, Vazire, & Oltmanns, 2011;Dufner et al, 2012;Dufner, Rauthmann, Czarna, & Denissen, 2013;Friedman, Oltmanns, Gleason, & Turkheimer, 2006, Wurst et al, in press), but studies showing longer-term costs of narcissism rather than short-term benefits have been rare, and both longitudinal studies (Leckelt, Küfner, Nestler, & Back, 2015;Paulhus, 1998) and investigations of wider interpersonal contexts are exceptions (Clifton, 2011;Czarna, Dufner, & Clifton, 2014;Küfner, Nestler, & Back, 2013).…”
Section: Narcissism and Popularitymentioning
confidence: 99%
“…However, studies examining the relation between narcissism and other‐derogation in the absence of ego threat have produced inconsistent results. One study reported null findings (South et al., ), whereas two studies reported significant findings (Lamkin, Clifton, Campbell, & Miller, in press; Wood, Harms, & Vazire, ). Recently, Back et al.…”
Section: Narcissism and Ego Threatmentioning
confidence: 99%